Abundant aftershock sequence of the 2015 Mw7.5 Hindu Kush intermediate-depth earthquake. Issue 2 (23rd January 2018) - Li, Chenyu; Peng, Zhigang; Yao, Dongdong; Guo, Hao; Zhan, Zhongwen; Zhang, Haijiang
SUMMARY: The 2015 M w 7.5 Hindu Kush earthquake occurred at a depth of 213 km beneath the Hindu Kush region of Afghanistan. While many early aftershocks were missing from the global earthquake catalogues, this sequence was recorded continuously by eight broad-band stations within 500 km. Here we use a waveform matching technique to systematically detect earthquakes around the main shock. More than 3000 events are detected within 35 d after the main shock, as compared with 42 listed in the Advanced National Seismic System catalogue (or 196 in the International Seismological Centre catalogue). The aftershock sequence generally follows the Omori's law with a decay constant p = 0.92. We also apply the recently developed double-pair double-difference technique to relocate all detected aftershocks. Most of them are located to the west of the hypocentre of the main shock, consistent with the westward propagation of the main-shock rupture. The aftershocks outline a nearly vertical southward dipping plane, which matches well with one of the nodal planes of the main shock. We conclude that the aftershock sequence of this intermediate-depth earthquake shares many similarities with those for shallow earthquakes and infer that there are some common mechanisms responsible for shallow and intermediate-depth earthquakes.